2012
DOI: 10.1002/j.1532-2149.2011.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Spouse‐assisted training in pain coping skills and the outcome of multidisciplinary pain management for chronic low back pain treatment: A 1‐year randomized controlled trial

Abstract: This study examined the comparative efficacy of three interventions: a spouse-assisted coping skills training protocol for patients undergoing a multidisciplinary pain management programme (SA-MPMP), conventional patient-oriented multidisciplinary pain management programme (P-MPMP) and standard medical care (SMC). Thirty-six chronic low back pain (CLBP) patients and their spouses were randomly assigned to one of the three conditions. The SA-MPMP condition consisted of seven, weekly, 2-h, group sessions of trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 43 publications
0
93
0
Order By: Relevance
“…RC led to the greatest improvements in interpersonal outcomes for couples, and had some of the strongest effect sizes overall, which suggests that this may be an important area of need for couples living with chronic illness. Another key observation was that many couples interventions achieved greater effects than the same or similar patient-only intervention across emotional [42], interpersonal [37,43,44], cognitive [41,49], and somatic outcomes [46,48]. This suggests that partner-inclusion may provide benefits beyond that of the content of the intervention itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RC led to the greatest improvements in interpersonal outcomes for couples, and had some of the strongest effect sizes overall, which suggests that this may be an important area of need for couples living with chronic illness. Another key observation was that many couples interventions achieved greater effects than the same or similar patient-only intervention across emotional [42], interpersonal [37,43,44], cognitive [41,49], and somatic outcomes [46,48]. This suggests that partner-inclusion may provide benefits beyond that of the content of the intervention itself.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies compared the couples intervention with a patient-only intervention [35,36,37,38,39,40], eight studies used a patient-only comparison group and a usual care control group [41,42,43,44,45,46,47,48], one study compared two types of couples interventions with a patient-alone comparison group [49], and the remaining twenty compared a couples intervention with usual care or waiting-list controls. Twenty-eight studies reported effect sizes, or provided information to calculate effect sizes.…”
Section: Main Descriptivesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an emerging growth of research that shows the inclusion of partners within treatment paradigms for chronic pain patients can be beneficial. 21 One key factor in having a supportive partner is the level of intimacy and empathy shown, 22 and it could be argued that the sexual union between partners, or lack of it as appears the case for those with CLBP, could be an important determinant of this social influence. Clinicians do routinely assess the impact CLBP has on their patient; our research suggests inquiry on the possible disruption of sexual activity due to CLBP may be a worthwhile additional question to highlight a potentially important psychosocial influence.…”
Section: Discussionmentioning
confidence: 99%
“…The pain-interaction process has been suggested as a mechanism which might explain the progression of acute to chronic pain in couples [77] and the nature of empathy between pain patients and their spouses has also been a specific focus of research [78,79]. Finally, interest in the role of significant others has simulated new approaches to intervention such as spouse-assisted coping skills training [80] and integrative behavioral couple therapy [81].…”
Section: Chronic Pain Rehabilitation: the Role Of Significant Othersmentioning
confidence: 99%